2019
DOI: 10.3390/jcm8112007
|View full text |Cite
|
Sign up to set email alerts
|

Advanced MRI Assessment during Dendritic Cell Immunotherapy Added to Standard Treatment Against Glioblastoma

Abstract: Evaluating changes induced by immunotherapies (IT) on conventional magnetic resonance imaging (MRI) is difficult because those treatments may produce inflammatory responses. To explore the potential contribution of advanced MRI to distinguish pseudoprogression (PsP) and true tumor progression (TTP), and to identify patients obtaining therapeutic benefit from IT, we examined aMRI findings in newly diagnosed glioblastoma treated with dendritic cell IT added to standard treatment. We analyzed longitudinal MRIs ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Changes in DWI parameters may also provide value in predicting immunotherapy response. Recently, Cuccarini et al found that up to 4 months after immunotherapy via dendritic cell vaccine, an increase in NK cell response was associated with a decrease in normalized minimum ADC (rADC min ) [54]. Interestingly, higher pre-vaccination rADC min , which is consistent with higher baseline permissiveness to immune cell infiltration, was associated with better PFS and OS [54].…”
Section: Gliomamentioning
confidence: 97%
See 3 more Smart Citations
“…Changes in DWI parameters may also provide value in predicting immunotherapy response. Recently, Cuccarini et al found that up to 4 months after immunotherapy via dendritic cell vaccine, an increase in NK cell response was associated with a decrease in normalized minimum ADC (rADC min ) [54]. Interestingly, higher pre-vaccination rADC min , which is consistent with higher baseline permissiveness to immune cell infiltration, was associated with better PFS and OS [54].…”
Section: Gliomamentioning
confidence: 97%
“…Currently, few biomarkers exist to measure the temporal response of tumors to immunotherapy. Recent studies have demonstrated the importance of radiomic measurements before and after treatment in predicting response to immunotherapy, specifically for checkpoint inhibition and dendritic cell therapy [34,[42][43]54]. Changes to FDG uptake features, rADCmin, and perinodular Gabor were shown to be associated with response and prognosis, and ought to be validated in future studies.…”
Section: Biomarker Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches aimed at overcoming this CNS tumor limitation have been described. Current evidence deriving from phase I and II trials suggests that DC vaccination may activate an immune response against CNS tumors (198)(199)(200)(201)(202). Although more than 500 GBM patients have been treated with DC vaccination and clinical results have been encouraging, there is not robust evidence of clinical efficacy, because of either the noncontrolled design of the studies or the low patient numbers.…”
Section: Vaccine-based Approachesmentioning
confidence: 99%